EARNINGS MANAGEMENT AND FUTURE EARNINGS - Simamora, Alex Johanes (Jurnal Akuntansi dan Keuangan Indonesia, 2019)
This research is aimed to examine the moderating effect of the cost of earnings management on the relationship between earnings management and future earnings. Research samples are manufacture companies listed in Indonesia Stock Exchange 2013-2015. The cost of accruals earnings management is auditor quality, while the costs of real earnings management are the market share and financial health. Based on the fixed effect regression test, auditor quality strengthens the positive effect of accruals earnings management on future performance, while market share and financial health weaken the negative effect of real earnings management on future earnings. It indicates that in the context of efficient contracting, high quality auditor provide better signal for earnings prediction compared to the low quality auditor. In addition, higher market share and higher financial health limit opportunistic real earnings management to reduce future earnings.